Organização social indígena da tribo Pakaanóva do município de Guajará-Mirim - Rondônia - Bernardo, Ismael Ferreira (2013)
The goal of this paper is to carry out a study about the indigenous social organization of the Pakaanóva people in the municipality of Guajará-Mirim, state of Rondônia. The thematic approach of this paper is the indigenous social organization. Its object of study is to describe the context and the variability of the new configurations of the indigenous society, that is, the new base of social organization in the Pakaanóva tribe. As specific goals, this study seeks to verify the relation between recent configurations of current indigenous socialization and their traditional versions and establish comparisons between the traditional social organization and the current indigenous model of the Pakaanóva tribe. The indigenous population presents various models of organization, the distinction of which is supposedly connected to the geographical, civilization and ethnic processes. According to the indigenous literature, the greatest leader that exists in the tribe is the chief, who coordinates the whole tribe and the shaman who is responsible for the ritual processes and is the existing shaman in the tribe. Indigenous organization is the way in which the indigenous people organize their work and divide their responsibilities, being part of daily life and of collective life. The methodology of research adopted was bibliographic, with emphasis on the indigenous peoples, specifically the Pakaanóva ethnic group. The information was collected through books, journals, articles, dissertations and materials available on the world network of computers. The conclusion presented in this paper reveals that the Pakaanóva indigenous people, in spite of adversities, still persist and try to maintain their social, economic, cultural and political institutions, even though only partially.